Farmers' practices, metapopulation dynamics, and conservation of agricultural biodiversity on-farm: a case study of sorghum among the Duupa in sub-sahelian Cameroon - Álvarez, N.; Garine, E.; Khasah, C.; Dounias, E.; Hossaert-McKey, M.; McKey, D. (2004)
In many traditionally managed agroecosystems, populations of domesticated plants maintain high levels of genetic diversity. The threat of erosion of this diversity is a current conservation concern, motivating studies of how diversity can be maintained by in situ conservation measures. Precisely how the biological traits of plants and the cultural practices of farmers act on fundamental evolutionary forces – drift, migration, selection, and mutation – to create and maintain crop plant diversity has been little investigated in detail. The authors develop some elements of the framework required for studying such biocultural interactions, focusing on one component of management: farmers' decisions on what to plant, and the structure of germplasm exchange among farmers. They illustrate the approach with a study of Duupa farmers in northern Cameroon. The results suggest that sorghum populations managed by the Duupa function like source–sink metapopulations. Fields of older farmers, larger and containing a greater number of varieties, act as sources, whereas fields of younger farmers act as sinks, becoming sources as their owners mature. In each field, seeds for sowing are selected from a small number of plants. The frequent exchange of germplasm among fields may counteract the genetic bottlenecks associated with the small number of genitors within each field. Identifying key processes and key individuals should facilitate the design of in situ conservation measures to maintain crop plant diversity against the threat of genetic erosion.